Integrasi Teknologi Digital dalam Pengajaran Kitab Kuning di Pesantren - Robiatul Adawiyah; Muhammad Husni (CV. Lentera Literasi Indonesia, 2026)
Traditional Islamic boarding schools (pesantren) in Indonesia have long relied on conventional methods to study the Kitab Kuning, such as sorogan, bandongan, and talaqqi, emphasizing direct interaction between teachers and students while instilling religious, moral, and ethical values. However, limitations in time, space, and the learning preferences of younger generations have prompted the integration of digital technology in learning. This study employs a qualitative approach with a case study strategy to explore the implementation of digital technology in Kitab Kuning teaching. Data were collected through participatory observation, in-depth interviews, and document analysis, then thematically analyzed. Findings indicate that digital integration such as e-learning, instructional videos, online forums, and digital repositories an expand access, enhance flexibility, and facilitate comprehension for students. The most effective model is hybrid or blended learning, which combines traditional methods with digital technology, maintaining traditional values while improving digital literacy. Nonetheless, challenges including limited infrastructure, inadequate digital skills of instructors, and potential weakening of face-to-face interaction require appropriate managerial strategies. Thus, digital technology integration not only supports the sustainability of Kitab Kuning learning but also addresses the needs of modern students and maintains the relevance of pesantren in the digital era.